Metacognitive Awareness in Engineering Students: SEM Analysis of Self-regulated Learning, Self Efficacy, and Learning Motivation - Hidayat, Hendra (Universitas Negeri Padang, 2022)
This study aims to explore the impact of self-regulated learning, self efficacy, and learning motivation on the metacognitive awareness of engineering students at the university level. A total of 358 students participated in the research, selected through purposive sampling. The participants had completed at least one semester of coursework, ensuring they had enough academic experience to reliably assess the study variables. Data was gathered via a survey and examined using Structural Equation Modeling (SEM) with the SmartPLS 3 software. Findings reveal that, in direct effect analysis, self-regulated learning and self efficacy do not significantly influence metacognitive awareness, whereas learning motivation does. However, in indirect effect analysis, both of them exert a significant impact on metacognitive awareness through the moderating role of learning motivation. These results suggest that self-regulated learning and self efficacy are not enough to spark awareness of one’s own thinking processes, motivation contributes importantly to this relationship.